Media Kompas TV dalam Mempengaruhi Pola Pikir Masyarakat pada Penanganan Covid -19 di Medan - Syamsidar, Cut (MASALIQ, 2023)
The purpose of this research is to find out how the community's mindset is in handling Covid-19 in Medan, North Sumatra, as well as to find out some of the obstacles and obstacles faced by Kompas TV as well as how Kompas TV deals with these obstacles. This research was conducted at the Kompas TV Medan office, Jalan K.H. Wahid Hasyim No. 37, Babura, Medan Baru District, North Sumatra 20153. In this study using qualitative research methods with a descriptive approach, namely a study that seeks to collect data, process, analyze and interpret qualitatively and describe or describe a number of variables related to problems and units researched. Data collection techniques are used with observation, interviews, and documentation. Then the results of this study are 1. Media Kompas TV in influencing the mindset of the people is trying several ways so that people believe in the Covid-19 virus which is currently spreading in the world including, the Indonesian terrain. Efforts are being made as routinely reporting the number of deaths, positives and also the number of those who have recovered because of this virus. Kompas TV also provides education on how to handle it through its publications. Of course, the appeal that Kompas is making to the public is in accordance with the recommendations of the government and medical personnel. 2. The obstacle faced by Kompas TV in influencing people's mindset in handling Covid-19 in the city of Medan is the difficulty of finding sources who want to meet in person to conduct interviews with Kompas TV. Officials are often opaque in conveying bed inventory data, available vaccine doses. 3. Kompas TV's way of dealing with obstacles that occur in influencing people's mindsets in handling Covid-19 is to look for other sources who are equally competent in the health sector. If there are obstacles such as officials who are not clear in conveying information, Kompas TV will re-check with the party concerned.